Legal Education on Legal Certainty Guarantee for Electronic Land Certificates in Batu Cermin Village, Komodo District Labuan Bajo, East Nusa Tenggara - I Made Pria Dharsana; I Gusti Agung Ayu Gita Pritayanti Dinar; Gregorius Yolan Setiawan (Lembaga Pengabdian Kepada Masyarakat, Universitas Warmadewa, 2026)
Land certificates are essential in investment as they serve as proof of legal ownership of the land. They ensure legal certainty for investors, safeguard land rights, and support various land-related investment activities. Therefore, it is important to have a thorough legal understanding of the legal certainty of electronic land certificates, which are currently being promoted by the Ministry of Agrarian and Spatial Planning/National Land Agency (ATR/BPN). Batu Cermin Village holds significant potential for global tourism due to its natural culture and attractions. Located in Komodo district within West Manggarai regency, East Nusa Tenggara province, Batu Cermin covers an area of 1555 km² and had a population of 7,000 in 2020. Tourism is a vital source of Regional Original Income for West Manggarai. The main attraction in this district is Taman Nasional Komodo (TNK). Additionally, Batu Cermin Cave is frequently included in tour packages as a popular tourist spot. The growth of tourism in Batu Cermin and nearby areas has attracted more local and international investors. Land certificates are essential for investment, serving as proof of legal ownership of the land involved.